(untitled) (Revista Direito em Debate, 2019)
This article aimed to identify the best relationship between judicial binding and the principle of the independence of the courts. In order to reach the proposed objective, the method of approach was the inductive one, being the data collection carried out through the technique of bibliographic research of secondary source. In the final considerations, it was concluded that the best relationship between judicial binding and the principle of the independence of the courts, remains established in the portuguese model, since it allows the judge an expansion of his imaginative perception and, consequently, helps in the formation of a more coherent Law.